2019
DOI: 10.1111/fcsr.12341
|View full text |Cite
|
Sign up to set email alerts
|

Parental Financial Socialization: Is Too Much Help Leading to Debt Ignorance among College Students?

Abstract: Evidence suggests that college students are unaware of their debt obligations. This study utilized the National Student Financial Wellness Study to examine whether aspects of financial parenting contribute to debt ignorance among college students. Reliance on parents for advice, parental financial support, and credit card payment responsibility were positively associated with ignorance of debt. Financial knowledge and working while in college reduced the likelihood of debt ignorance. We discuss implications fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 37 publications
(59 reference statements)
2
19
0
1
Order By: Relevance
“…We assume that student–parents who must juggle caring for their dependent child, paying for childcare, and their family’s cost of living, find refuge in having a source of financial resources that can aid their current situation. According to Letkiewicz, Lim, Heckman, and Montalto (2019), “Dramatic increases in undergraduate tuition, fees, and other expenses have amplified both the incidence and magnitude of student debt in the United States (p. 149).” Given the detrimental outcomes that are created in the lives of young adults due to student loan debt (see Heckman et al, 2014; Robb, 2017), we encourage institutions of higher education to find ways to financially support student–parents on their campus.…”
Section: Discussionmentioning
confidence: 99%
“…We assume that student–parents who must juggle caring for their dependent child, paying for childcare, and their family’s cost of living, find refuge in having a source of financial resources that can aid their current situation. According to Letkiewicz, Lim, Heckman, and Montalto (2019), “Dramatic increases in undergraduate tuition, fees, and other expenses have amplified both the incidence and magnitude of student debt in the United States (p. 149).” Given the detrimental outcomes that are created in the lives of young adults due to student loan debt (see Heckman et al, 2014; Robb, 2017), we encourage institutions of higher education to find ways to financially support student–parents on their campus.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers on financial literacy and financial well-being argue that consumers are faced with complex financial decisions from the start of adulthood, the consequences of which may affect them for years to come (Lusardi et al, 2010 ). So studies, like those by Letkiewicz et al ( 2019 ), Mendes-Da-Silva et al ( 2012 ), Norvilitis & Mendes-Da-Silva ( 2013 ), have examined the predictors of the indebtedness and financial well-being of young adults, with the intention of identifying positive financial habits (OECD, 2020 ). Research in this field is both relevant and timely, because evidence indicates that financial well-being is associated with both lower levels of stress and higher levels of satisfaction with life and, in extreme cases, personal financial crises have been a motive for suicide (Ming & Chen, 2021 ; Mae, 2005 ; Norvilitis & Santa Maria, 2002 ; Norvilitis et al, 2003 ).…”
Section: Motivationmentioning
confidence: 99%
“…The very existence of financial literacy in individuals has demonstrated that it improves financial decisions and perceived well-being (Ahmad et al, 2017). Thus, the crucial component to strengthening one's financial well-being is preparing knowledge about financial obligations (Letkiewicz et al, 2019). It is because individuals, in general, develop product knowledge in terms of usage, especially in credit card, through information search, use and experience (Johan & Putit, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ignorance is defined in Merriam-Webster (2021) as "lack of knowledge, education, or awareness". Ignorance in the context of this study means ignorance or confusion among credit card users regarding the characteristics, costs and impacts on obligations and responsibilities as debtors that can cause financial problems such as overdue loans and result in adverse effects on financial well-being (Seira et al, 2017;Letkiewicz et al, 2019;Zainudin et al, 2019).…”
Section: Theme 3: Ignorancementioning
confidence: 99%